A Brighter Word Than Bright : Keats at Work - Beachy-Quick, Dan, 1973- (Book collections on Project MUSE., 2013)
The Romantic poet John Keats, considered by many as one of the greatest poets in the English language, has long been the subject of attention from scholars who seek to understand him and poets who seek to emulate him. Bridging these impulses, this book is neither historical biography nor scholarly study, but instead a biography of Keats's poetic imagination. Here the author, a poet, enters into Keats's writing - both his letters and his poems - not to critique or judge, not to claim or argue, but to embrace the passion and quickness of Keats's poetry.